SUSTAINABLE DESIGN FOR SCHOOL BUILDINGS IN ALBANIA - KEY PRINCIPLES - Lika, Anxhela (European Scientific Journal, ESJ, 2014)
The current situation of schools in Albania is such that there is an urgent need for reconstruction of existing schools and building new schools to meet the needs of the constantly growing number of students and the needs of increasing school standards in accordance with the time.Few of these schools ,meet the minimum norms on the basis of criteria which must be designed and built a school . In schools built and reconstructed after 90 years , it is noted a significant improvement in terms of quality of construction . But it must be said that this improvement still needs work . So it is very difficult to speak about sustainable schools in Albania ,because we don’t have any till now.This article presents precisely the main design principles of a sustainable school ( so necessary for the situation in Albania ) , conditions that must be met ,so that this kind of design typology be durable and efficient in many aspects.The principles that are treated here include the following main points : 1 - Functionality and flexibility. 2 - Aesthetic treatment. 3 - Climate Comfort. 4 - Climate control and ventilation. 5 - Natural and artificial lighting. 6 – Acoustics. 7 – Energy efficiency .